IOT connected safety helmet for noise hazard protection / Muhammad Afif Asuadi and Khairul Amirin Ridzuan - Asuadi, Muhammad Afif; Ridzuan, Khairul Amirin (2019)
Current situation now that have a problem about hearing. Many of workers according to statistics from Center of Disease Control and Prevention, 17% of workers expose to hazardous noise each year. This project was created to redesign the safety helmet by adding additional safety precautions measures using the relevance technique by using IoT and to develop a system to monitor the use of safety helmet at the noisy workplaces. NodeMCU is used as microcontroller to select the output depending on user’s input selection. Sound sensor is used to detect the noise and the system will operate the components such as vibrator motor and LED. The value of the output will display at laptop and also send the information through Telegram. Result indicated that this project achieved the objective to protect from noise hazard. Further improvement can be made by modified it be more easy to use and more high quality.